2021
DOI: 10.1525/cse.2021.1434075
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Impacts to National Park Visitation From COVID-19

Abstract: Yosemite National Park is a popular tourist destination with high visitation levels that have increased throughout the summer season over the past several decades. Like with other protected areas, high visitation levels pose challenges for coordinating resources, infrastructural capacity, and visitor experiences. Use limits, including rationing vehicle entry at gates by reservation, are one possible strategy to manage visitation levels. After an initial full closure, the park chose to operationalize a multipha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In addition, the included articles differed as to the effect of lockdown restrictions on visitation, with ten reporting both increases and decreases ( [17] , [19] , [30] , [36] , [37] , [47] , [57] , [60] , [89] , [91] ). Seven studies reported that GI use decreased during lockdown ( [7] , [13] , [31] , [40] , [41] , [48] , [49] ) while three studies reported that use increased during lockdown but decreased as restrictions were eased ( [13] , [20] , [29] ), or that GI use increased during school, gym, and entertainment venue closures ( Curtis et al, 2021 ), suggesting that GI was used as a stopgap to replace other activities that resumed as lockdowns eased.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the included articles differed as to the effect of lockdown restrictions on visitation, with ten reporting both increases and decreases ( [17] , [19] , [30] , [36] , [37] , [47] , [57] , [60] , [89] , [91] ). Seven studies reported that GI use decreased during lockdown ( [7] , [13] , [31] , [40] , [41] , [48] , [49] ) while three studies reported that use increased during lockdown but decreased as restrictions were eased ( [13] , [20] , [29] ), or that GI use increased during school, gym, and entertainment venue closures ( Curtis et al, 2021 ), suggesting that GI was used as a stopgap to replace other activities that resumed as lockdowns eased.…”
Section: Resultsmentioning
confidence: 99%
“…In line with a shift towards more local GI during the pandemic, accessing GI on foot also increased as driving generally decreased ( [19] , [84] , [83] ). Jenkins et al (2021) assessed how Yosemite National Park implemented restrictions on visitors during the pandemic and reported that park managers implemented a day-use and online permit system and suspended “walk-up” reservations. This change in access was used to limit the park’s capacity to roughly 50%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations